The adaptation into Spanish of the Coddington Life Events Scales (CLES). - Villalonga-Olives, E; Valderas, J; Palacio-Vieira, J; Herdman, M; Rajmil, L; Alonso, J (2008)
AIMS: To obtain a conceptually and psychometrically equivalent Spanish version of the Coddington Life Events Scales (CLES) for children and adolescents and to test their psychometric properties. METHODS: Forward and backward translations were performed. Comprehension, acceptability, and alternative translations were tested in focus groups and semi-structured interviews. An expert panel and the copyright holders of the original version were actively involved. Test-retest reliability [Intraclass Correlation Coefficient (ICC)] was assessed by administering the questionnaire on two occasions 3 months apart to children aged 12-14 years (n = 30). Construct validity was assessed by comparing children's responses with those of their parents (n = 19). The methods replicated those of the validation of the original version. RESULTS: Of the 53 CLES items translated, ten were found to be difficult to understand. Following back-translation, seven items were modified and a final version was obtained. Test-retest ICC reliability for total scores was 0.63. The ICC between children and parents was 0.42. Both results were very similar to those reported for the original version. CONCLUSIONS: These preliminary findings suggest that the Spanish version of the CLES is understandable and acceptable and that it is similar to the original in terms of validity and reliability. Although further validation is needed, it is recommended for use in research settings in Spain.